ASSOCIATION OF RED CELL DISTRIBUTION WIDTH (RDW) TO SERUM ALBUMIN RATIO WITH PROGNOSIS OF CORONARY HEART DISEASE(CHD) IN PATIENTS WITH ACUTE CORONARY SYNDROME (ACS). (The Research of Medical Science Review, 2025)
Objective: To determine the association between RDW to Albumin ratio and prognosis of acute coronary syndrome (ACS) in form of all-cause Mortality in patients admitted in ICU, CCU or Medicine Department. Study Design: Prospective Cohort Study.Study Setting: The Study was planned at Department of Internal Medicine and Cardiac Care Unit (CCU), Recep Tayyip Erdogan Indus Hospital, Muzaffargarh.Study Duration: From September’2024 to Febuary’2025.Methodology: This study enrolled 126 patients using non-probability consecutive sampling, categorized into high RAR (≥3.5) and low RAR (<3.5) groups. Demographics, clinical data, RDW, and albumin levels were recorded at admission. Patients were followed for 90-day all-cause mortality. Results: Mean age was 52.29 ± 19.64 years, and 57.9% were male. The 90-day mortality rate was 12.7%. Mortality was significantly higher in the high RAR group (19.0%) versus the low RAR group (6.3%) with RR = 3.471 (p = 0.032). Subgroup analysis showed higher mortality among older patients, females, diabetics, hypertensives, and those with a positive family history of ischemic heart disease(IHD). Conclusion: High RAR is a significant, low-cost biomarker associated with increased short-term mortality in ACS patients. It may serve as an early prognostic indicator to improve risk stratification and guide targeted interventions.